Computationally Driven Discovery of a Family of Layered LiNiB Polymorphs. (26th September 2019) - Gvozdetskyi, Volodymyr; Bhaskar, Gourab; Batuk, Maria; Zhao, Xin; Wang, Renhai; Carnahan, Scott L.; Hanrahan, Michael P.; Ribeiro, Raquel A.; Canfield, Paul C.; Rossini, Aaron J.; Wang, Cai‐Zhuang; Ho, Kai‐Ming; et al.
Abstract: Two novel lithium nickel boride polymorphs, RT ‐LiNiB and HT ‐LiNiB, with layered crystal structures are reported. This family of compounds was theoretically predicted by using the adaptive genetic algorithm (AGA) and subsequently synthesized by a hydride route with LiH as the lithium source. Unique among the known ternary transition‐metal borides, the LiNiB structures feature Li layers alternating with nearly planar [NiB] layers composed of Ni hexagonal rings with a B–B pair at the center. A comprehensive study using a combination of single crystal/synchrotron powder X‐ray diffraction, solid‐state 7 Li and 11 B NMR spectroscopy, scanning transmission electron microscopy, quantum‐chemical calculations, and magnetism has shed light on the intrinsic features of these polymorphic compounds. The unique layered structures of LiNiB compounds make them ultimate precursors for exfoliation studies, thus paving a way toward two‐dimensional transition‐metal borides, MBenes. Abstract : Designerschichten : Neuartige Lithiumnickelboride mit einzigartigen Schichtstrukturen wurden theoretisch vorhergesagt und synthetisiert. Ihre Strukturen bestehen aus [NiB]‐Schichten mit unterschiedlichen Topologien, die sich mit Schichten von Li‐Kationen abwechseln (siehe Bild). Diese Verbindungen sind Vorläufer für die weitere Exfoliation zur Erzeugung von 2D‐Übergangsmetallboriden, bekannt als MBene.